PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENERIMAAN DAERAH KABUPATEN SUMBAWA - Hikmawan Sapitri; I Nyoman Sutama (Jurnal Ekonomi & Bisnis, 2022)
This research was conducted with the aim of knowing the effect of economic growth on regional revenues in Sumbawa Regency. This research is a causal associative research, which aims to determine the effect of economic growth on regional revenues in Sumbawa Regency. The type of data used is quantitative data in the form of data on economic growth and regional revenue for Sumbawa Regency for 2017-2021 obtained from Dinas Pendapatan, Pengelolaan Keuangan, dan Aset Daerah (DPKA), Badan Pusat Statistik (BPS) for Sumbawa Regency. All data that has been collected will be processed using the SPSS program to be studied using techniques that include simple linear regression analysis, individual parameter hypothesis testing (t test) and determinant coefficient test (R2). Based on the results of the research that has been done, it can be concluded that economic growth has a positive and significant effect on regional revenues in Sumbawa Regency. The ability of the economic growth variable to affect the variation in the regional revenue variable in Sumbawa Regency is 89.5%, while the remaining 10.5% is explained by variables outside the model which are summarized in random errors, such as regional loans and regional expenditures.